ANALISIS PERAWATAN SISTEM COAL PULVERIZER MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI PLTU BANTEN 1 SURALAYA 8 - Sukmawati, Sri; Setyo Rini, Asih; Adi Saputra, Petrus Canisius (LPPM Universitas Bina Bangsa, 2024)
Banten 1 Suralaya Power Plant is a Coal-Fired Steam Power Plant. The issue at hand is the high downtime of the coal pulverizer system, which experienced 195 failures across the seven coal pulverizer systems in 2023, resulting in a total downtime of 1,020.3 hours. This research focuses on Coal Pulverizer System C, which had the highest downtime, averaging 274 hours in 2023. The aim is to identify the factors causing the failures and to propose a maintenance scheduling plan. This research employs the Reliability Centered Maintenance method, which is a logical engineering process to determine maintenance tasks that will ensure a reliability system design under specific operating conditions in a particular operational environment using a downtime analysis approach. The proposed maintenance scheduling is based on the calculations of Mean Time Between Failure and Mean Time To Repair. Based on the downtime analysis, it is known that the performance of the Coal Pulverizer C system is still optimal with an average availability of 94%. A failure mode of the Coal Feeder component was identified with an RPN of 320 as the dominant cause of the damage. Additionally, from the Function Block Diagram and Logic Tree Analysis, 2 failure modes were found in category B (Outage Problem) and 5 failure modes in category C. (Economic Problem). With the Reliability Centered Maintenance method based on the calculations of Mean Time Between Failure and Mean Time To Repair, a maintenance schedule is proposed for the components of the Coal Pulverizer System C, namely: Pulverizer Body every 115 days, Pulverizer Motor every 76 days, Lube Oil System every 15 days, Coal Feeder every 25 days, Coal Feeder Motor every 57 days, Control Instrument & Indicator System for Pulverizer every 32 days, and Control Instrument & Indicator for Coal Feeder every 46 days.